Tissue-Resident Memory-Like CD8+ T Cells Exhibit Heterogeneous Characteristics in Tuberculous Pleural Effusion - Sifei Yu; Suihua Lao; Binyan Yang; Changyou Wu (Journal of Immunology Research)
Tissue-resident memory T (TRM) cells are well known to play critical roles in peripheral tissues during virus infection and tumor immunology. Our previous studies indicated that CD69+CD4+ and CD69+CD8+ T cells in tuberculous pleural effusion (TPE) were antigen-specific memory T cells. However, the phenotypical and functional characteristics of CD8+ TRM cells in tuberculosis remain unknown. We found that CD103+CD8+ T cells were the predominant subset of CD103+ lymphocytes in TPE; both CD103 and CD69 expressed on memory CD8+ T cells from TPE were significantly increased compared with those from paired peripheral blood. Phenotypically, CD103+CD69+ and CD103+CD69-CD8+ T cells expressed higher levels of CD45RO than CD103-CD69+CD8+ T cells did; CD103+CD69-CD8+ T cells highly expressed CD27, CD127, and CD62L and some chemokine receptors. We further compared the functional differences among the four distinct CD45RO+CD8+ T subsets identified by CD103 and CD69 expression. In consist with our published results, CD69+CD8+ T cells, but not CD103+CD8+, produced high levels of IFN-γ after treatment with BCG in the presence of BFA. Nevertheless, CD103-CD69+ and CD103+CD69+ memory CD8+ T cells expressed higher levels of Granzyme B, while CD103+CD69- memory CD8+ T cells were characterized as a possibly immunosuppressive subset by highly expressing CTLA-4, CD25, and FoxP3. Furthermore, TGF-β extremely increased CD103 expression but not CD69 in vitro. Together, CD103+CD8+ T cells form the predominant subset of CD103+ lymphocytes in TPE; CD103 and CD69 expression defines distinct CD8+ TRM-like subsets exhibiting phenotypical and functional heterogeneity. Our findings provide an important theoretical basis to optimize and evaluate new tuberculosis vaccines.